TP53 Abnormalities and MMR Preservation in 5 Cases of Proliferating Trichilemmal Tumours - Raquel Martín-Sanz; José María Sayagués; Pilar García-Cano; Mikel Azcue-Mayorga; María del Carmen Parra-Pérez; María Ángeles Pacios-Pacios; Enric Piqué-Durán; Jorge Feito (MDPI AG, 2021)
Proliferating trichilemmal tumours (PTT) are defined by a benign squamous cell proliferation inside a trichilemmal cystic (TC) cavity. A possible explanation of this proliferative phenomenon within the cyst may be molecular alterations in genes associated to cell proliferation, which can be induced by ultraviolet radiation. Among other genes, alterations on TP53 and DNA mismatch repair proteins (MMR) may be involved in the cellular proliferation observed in PTT. Based on this assumption, but also taking into account the close relationship between the sebaceous ducts and the external root sheath where TC develop, a MMR, a p53 expression assessment and a TP53 study were performed in a series of 5 PTT cases, including a giant one. We failed to demonstrate a MMR disorder on studied PTT, but we agree with previous results suggesting increased p53 expression in these tumours, particularly in proliferative areas. TP53 alteration was confirmed with FISH technique, demonstrating TP53 deletion in most cells.